КОРПОРАТИВ МАЪЛУМОТЛАР АЛМАШИНУВИ ЖАРАЁНЛАРИДА СЕРВЕР КЛАСТЕРЛАРИ ЮКЛАМАЛАРИНИ ТАҚСИМЛАШНИНГ ҚАРОРЛАР ДАРАХТИГА АСОСЛАНГАН УСУЛИ - Асқаралиев, О.У. (SCIENCE and SOCIETY, 2025)
The article examines the issues of balancing computing loads of a server complex in the mode of corporate information exchange. In corporate data exchange processes, a decision tree-based method of server cluster load distribution was proposed, as a result of which the load balancing problem was solved.